2022
DOI: 10.1177/15593258211050532
|View full text |Cite
|
Sign up to set email alerts
|

Mesoporous SBA-15 Silica–Loaded Nano-formulation of Quercetin: A Probable Radio-Sensitizer for Lung Carcinoma

Abstract: Lung cancer is considered as one of the most serious disease worldwide. The progress of drug carriers based on nonmaterial, which selectively hold chemotherapeutic agents to cancer cells, has become a major focus in biomedical research. This study aimed to evaluate the growth inhibition and apoptosis induction of the human lung cancer cells (A-549) by Q-loaded SBA-15 conjugate system. Mesoporous silica nanoparticles (SBA-15) as host materials for transporting therapeutics medicaments were fabricated for target… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 43 publications
(55 reference statements)
0
6
0
Order By: Relevance
“…When NPs are conjugated with various cytotoxic drugs, the presence of folate favors the NPs incorporation by tumoral cells. For instance, NPs conjugated with doxorubicin, 69 methotrexate, 70 or quercetin 71,72 have been shown to exert enhanced therapeutic effects compared to NPs without folate.…”
Section: Resultsmentioning
confidence: 99%
“…When NPs are conjugated with various cytotoxic drugs, the presence of folate favors the NPs incorporation by tumoral cells. For instance, NPs conjugated with doxorubicin, 69 methotrexate, 70 or quercetin 71,72 have been shown to exert enhanced therapeutic effects compared to NPs without folate.…”
Section: Resultsmentioning
confidence: 99%
“…They showed that the PI3K/AKT/mTOR pathway acts as the apoptotic signaling in A549 cells. 104 Titanium dioxide nanotubes (TNT) have more significant surface space for carrier particles with exceptional physical and chemical features. The effect of conjugated TNT with quercetin (TNT-Qu) on the B16F10 animal melanoma model proved that topical TNT-Qu could be applied to reduce tumor growth via regulating phospho-STAT3 levels in the tumor.…”
Section: Quercetinmentioning
confidence: 99%
“…The biological examination of the A549 cancer cell line indicated the higher efficacy of Q‐SBA‐15 than quercetin alone. They showed that the PI3K/AKT/mTOR pathway acts as the apoptotic signaling in A549 cells 104 …”
Section: Advancements In Natural Substance Enhancement Through Nanote...mentioning
confidence: 99%
“…Alkahtani et al explored SBA-15 material for loading quercetin, where the synthesized quercetin loaded SBA-15 conjugate (Q-SBA-15 NP) demonstrated increased anticancer efficacy against lung carcinoma. 48 MSU are synthesized using nonionic surfactants at neutral or mild acidic pH conditions. The MSU structural assembly is similar to MCM-41; however, it does not reveal the long-range periodicity.…”
Section: Mesoporous Silica Nanoparticles (Msn) Synthesis Structure An...mentioning
confidence: 99%
“…Synthesis method of SBA-15 includes initially the dissolution of template Pluronic P123 in acidic conditions and then addition of silica precursor, which results in synthesis of silica having 2-D array with long 1-D channel structure. , Generally, SBA-15’s pore size varies from 4 to 12 nm, but adding swelling agents, i.e., 1,3,5 trimethylbenzene (TMB), results in increasing the pore size up to 30 nm. Alkahtani et al explored SBA-15 material for loading quercetin, where the synthesized quercetin loaded SBA-15 conjugate (Q-SBA-15 NP) demonstrated increased anticancer efficacy against lung carcinoma …”
Section: Mesoporous Silica Nanoparticles (Msn) Synthesis Structure An...mentioning
confidence: 99%